Self-Confidence Analysis in High School Students' Mathematics Learning - Ramadhani, Nur Indah; Muhammad Izzuddin Ramli; Diyah Purwati Cahyaningrum; Fauzi Mulyatna (International Journal of Asian Education, 2025)
Self-confidence is an important psychological factor that influences students' success in learning mathematics. Mathematics is often perceived as a difficult subject, which can lead to anxiety, hesitation, and low self-confidence among senior high school students. This study aims to analyze students' self-confidence in mathematics learning and identify the factors influencing it. The research employed a descriptive qualitative method involving senior high school students as research subjects. Data were collected through observation, questionnaires, and interviews to obtain a comprehensive description of students' self-confidence. The results indicate that some students demonstrated low levels of self-confidence, characterized by fear of making mistakes, lack of courage to ask questions, and passive participation during learning activities. Factors affecting students' self-confidence include previous learning experiences, teaching methods, and the learning environment. Therefore, supportive, innovative, and student-centered learning strategies are needed to enhance students' self-confidence in mathematics learning. The study concludes that improving students' self-confidence can contribute positively to their mathematics learning outcomes